History of the Concept of Similarity in Natural Sciences - Grigoriadou, Virginia John; Coutelieris, Frank A.; Theologou, Kostas (Conatus - Journal of Philosophy, 2021)
The concept of similarity has been discussed by many scientists and philosophers since ancient times. Thales of Miletus, Euclid, Aristotle, Galileo, Newton, Edgar Buckingham, and the modern philosopher of science Susan G. Sterrett are examples of intellectuals who perceived and examined the concept of similarity, while many scientists incorporated it in their scientific methodology. The wide range and variety of definitions of similarity could result in confusion regarding the meaning of the concept, the role the similarity mechanism plays in scientific methodology, and the identification of scientific fields to which similarity could be applied. The main aim of this paper was to enhance the understanding of the notion of similarity. To this end, we examined the historical evolution of the concept of similarity and the utilization of the mechanism of similarity in various eras of human intellectual activity, ranging from antiquity to the present day. In this context, the research hypothesis we investigated was the existence of specific and distinct stages of evolution within the long history of the concept of similarity in parallel with the evolution of scientific thought. A core question that motivated our work was when and under which conditions did the transition from the “technocratic” utilization of similarity (i.e., the use of similarity as a solution for practical problems) to its theoretical documentation and its conscious and systematic use as a significant experimental tool occurred. Another important question examined was whether there was a certain era that favored the development of the concept of similarity more than other historical periods. In order to address this hypothesis and respond to these questions, we sought to trace the evolution of conceptualizing and using similarity in different spatial and temporal contexts, formed by the corresponding historical, institutional, religious, and social conditions as well as the characteristics of the scientific methodology established during the period the similarity concept evolved.